The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1984
DOI: 10.1128/jcm.19.2.187-190.1984
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of bacteria in cerebrospinal fluid and blood of children with meningitis and its diagnostic significance

Abstract: Cerebrospinal fluid (CSF) specimens from pediatric patients with meningitis were examined for their concentration of microbes and the relationship of this count to the bacteremia levels, microscopy results, and polymorphonuclear leukocyte concentration. A total of 2,031 consecutive CSF specimens were analyzed, of which 63 (3.1%) were positive by culture from the same number of patients. We observed that 85% of the total CSF specimens positive for Haemophilus influenza type b, Streptococcus agalactiae, Streptoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0
4

Year Published

1989
1989
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(45 citation statements)
references
References 16 publications
2
39
0
4
Order By: Relevance
“…Previous studies of apheresis PLTs retested by culture at outdate provide limited insight into when contaminated units grew to high titers and what ultimate titer was attained. In this study, in seven of the nine cases detected by PGD, contaminating bacteria were shown to be at concentrations that were at least 10 5 CFU/mL based on detection by Gram stain 8,30 . These findings suggest that PLT doses had been held for sufficient lengths of time to allow low levels of contaminating bacteria to grow to dangerous titers, occurring in four units that were 3 days old and two that were 4 days old.…”
Section: Discussionmentioning
confidence: 50%
“…Previous studies of apheresis PLTs retested by culture at outdate provide limited insight into when contaminated units grew to high titers and what ultimate titer was attained. In this study, in seven of the nine cases detected by PGD, contaminating bacteria were shown to be at concentrations that were at least 10 5 CFU/mL based on detection by Gram stain 8,30 . These findings suggest that PLT doses had been held for sufficient lengths of time to allow low levels of contaminating bacteria to grow to dangerous titers, occurring in four units that were 3 days old and two that were 4 days old.…”
Section: Discussionmentioning
confidence: 50%
“…Initially the population size is small, so selection is inefficient and the population-wide mutation rate is low. However, the eventual carrying capacity of the blood and CSF are large enough (>1.5×10 5 ) [34, 35] for beneficial mutations to fix rapidly. Due to the short generation time of around an hour [36], this carrying capacity is reached early in the course of the disease (after 1-2 days) [37].…”
Section: Resultsmentioning
confidence: 99%
“…Our universal PCR was determined to have a sensitivity of 10 gram-negative bacteria (e.g., E. coli) and 250 gram-positive bacteria (e.g., S. aureus). Therefore, it would be adequate for detection of bacteria in CSF specimens, since 85% of CSF samples with bacterial infection contained more than 10 3 CFU of bacteria/ml (8). Although detection of bacterial pathogens in serum or whole blood by PCR has been reported (5,12,16), the universal PCR developed in this study may not have sufficient sensitivity for blood specimens, because the number of organisms in the blood is usually quite low.…”
Section: Discussionmentioning
confidence: 92%